A sliding-bulge structure at the Dicer processing site of pre-miRNAs regulates alternative Dicer processing to generate 5′-isomiRs. Issue 9 (September 2016) - Ma, Hongming; Wu, Yonggan; Niu, Qi; Zhang, Junli; Jia, Gengxiang; Manjunath, N.; Wu, Haoquan
Abstract: 5′-isomiRs expand the repertoire of miRNA targets. However, how they are generated is not well understood. Previously, we showed that for some miRNAs in mammalian cells, Drosha cleaves at multiple sites to generate multiple pre-miRNAs that give rise to multiple 5′-isomiRs. Here, we showed that for some other miRNAs, 5′-isomiRs are generated by alternative Dicer processing. In addition, we showed that in miR-203, alternative Dicer processing is regulated by a conserved sliding-bulge structure at the Dicer processing site, which allows the pre-miRNA molecule to fold into two different structures that are processed differently by Dicer. So far no RNA motif that slides to change conformation and alter a protein–RNA interaction has been reported. Thus, our study revealed a novel RNA motif that regulates 5′-isomiR generation in some miRNAs. It might also contribute to regulating protein–RNA interactions in other biological processes, since it takes only one point mutation to generate the sliding bulge, and there are a large number of different RNAs in the cell.